2015
DOI: 10.1080/14786419.2015.1060593
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of different parts of Pistacia khinjuk Stocks fruit and its correlation to phenolic composition

Abstract: The fruits of Pistacia khinjuk Stocks were collected from Ilam province, Iran. The aim of this study was to analyse antioxidant capacity and phenolic composition of different parts of P. khinjuk fruit. The antioxidant capacity of extracts was measured using different assays: ferric reducing ability of plasma, 2,2-diphenyl-1-picrylhydrazyl and nitric oxide radical scavenging. The phenolic composition of P. khinjuk fruit is reported for the first time. Amongst different parts of the fruit analysed in this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…These products could be a good source of anticholinesterase compounds (Hacıbekiroğlu et al 2015), and have antioxidant and urease inhibitory activity (Asghar Hatamnia et al 2015;Uddin et al 2015). Different studies evaluated species and subspecies of pistachios to find their ecological distribution and their karyotype (Ayaz & Namli 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These products could be a good source of anticholinesterase compounds (Hacıbekiroğlu et al 2015), and have antioxidant and urease inhibitory activity (Asghar Hatamnia et al 2015;Uddin et al 2015). Different studies evaluated species and subspecies of pistachios to find their ecological distribution and their karyotype (Ayaz & Namli 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial properties of the native species are known [ 10 , 11 , 12 ]. The use of different species of Pistachio as antibacterial, antifungal, antiviral, anti-atherogenic, hypoglycemia, antitumor and facilitating hepatic function is known [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Mastic and extracts of gum mastic have been used in traditional medicine for more than 5000 years as a dietary extract for the treatment of digestive disorders, 3 and its properties have been further examined in recent years. In vitro and experimental in vivo studies demonstrated that mastic and its extract have antitumor properties; [4][5][6] antibacterial, antifungal, and antiviral activities; [7][8][9][10][11][12][13][14] antioxidant activity; [15][16][17][18][19][20] analgesic activity; 21 and anti-inflammatory activities. [22][23][24][25] Based on this large number of potentially beneficial effects, it is currently in use in health care products and in the food industry.…”
mentioning
confidence: 99%